Correct administration aid for oral liquid medicines: Is a household spoon the right choice? - Younas, Eman; Fatima, Moomna; Alvina, Ayesha; Nawaz, Hafiz Awais; Anjum, Syed Muneeb; Usman, Muhammad; Pervaiz, Mehak; Shabbir, Amara; Rasheed, Huma (Frontiers in Public Health, 2023)
Background Correct medicine dosing is an important component in the safe and effective delivery of medicines, particularly for the pediatric population. However, there is a scarcity of public campaigns on the correct administration and choice of dosing aids for oral liquid dosage form in many countries, leading to medicine safety issues and therapeutic failures. Methods The study targeted the assessment of the knowledge and practice of university students. It utilizes pre- and post-intervention surveys administered through google forms as a survey tool during online zoom and in-person sessions. The intervention included a short video presentation detailing the selection and use of medicine spoons and other aids for the administration of oral liquid dosage. The Fischer Exact test was used to assess the pre- and post-test shift of responses. Results Nine-degree programs were engaged in the activity, and 108 students attended this health awareness activity after obtaining formal consent. A significant decline (CI = 95%, ****p-value < 0.05) in the choice of selecting tablespoon and a shift to a low-volume spoon, as well as rejection of an entire variety of household spoons, were observed. A significant improvement in the correct naming of spoons, the meaning of the abbreviation “tsp,” and the correct volume of a standard teaspoon were also observed with a p-value of <0.001. Conclusion A deficit in the knowledge of the proper use of measuring devices for oral liquid medicines in the educated population was observed, which can be enhanced through simple tools like short video presentations and awareness seminars.